Zone of historical monuments Santiago de Querétaro. An experience of cultural heritage management in Mexico - Guillén Alarcón, Plinio (2018)
The Historic Monuments Zone of Santiago de Querétaro (ZMHQ) is one of the 10 Mexican historical centers that has been inscribed into the World Heritage list of UNESCO. This inscription was achieved thanks to the development of a series of projects that looked for the recovery and preservation of this zone, which contains the traces of a series of relevant historical facts in the formation of the United States of Mexico. Within this process, and the incentive of the nomination as World Heritage, the need of comprehensive management tool that would allow for the protection of the ZMHQ became evident, or, more so, for the revitalization of this zone. However, the bibliographical review concludes that this objective has not been achieved, despite the existence of a normative and management framework, which was developed in the three levels of Mexican government (Federal, National and Municipal). The positive and negative experiences the management of the ZMHQ should allow us to rescue a series of important aspects of management. These could be useful later on, to carry out evaluations in other territorial settings, such as Peru.